On the typification of Cocculus platiphyllus and synonymization of Cocculus platiphyllus var. ildefonsianus with Curarea crassa (Menispermaceae) - Feliz, Pablo Fernando; Fernandes, Thiago; Braga, João Marcelo Alvarenga (Phytotaxa, 2024)
We designate here a lectotype and an epitype for Cocculus platiphyllus, and discuss about the identity of Cocculus platiphyllus var. ildefonsianus, including its lectotypification and synonymization with Curarea crassa.